DETERMINANTS OF NEONATAL PAIN MANAGEMENT PRACTICES AMONG NURSES WORKING IN NEONATAL CARE UNITS IN WESTERN KENYA HOSPITALS - Damaris Ongori; Teresa Okiri (Nurse and Health)
Background: Newborn babies in the neonatal intensive care units (NICU) and newborn units (NBUs) undergo various tissue-damaging procedures as a result of both diagnostic and therapeutic care. Each neonate may experience an average of 300 painful procedures throughout their period hospitalization surgeries inclusive. However, little is known about factors that determine the neonatal pain management practices among nurses working in NICUs in Kenya.